Iatrogenic descending thoracic aorta perforation by pedicle screws as a delayed complication of scoliosis correction surgery. The anesthetic management and TEE role - Ahmed Elrefaey (Saudi Journal of Anaesthesia)
A 29-year-old lady was referred to us with a rare complication of scoliosis correction surgery. She had two of the screws migrated and penetrated the descending thoracic aorta. She came to theater to have the screws removed and the aorta repaired endovascularly. The successful intervention needed a multidisciplinary team planning, coordinated work, and communication between the four involved teams: anesthesia, vascular surgery, interventional radiology, and spine surgery. There was a lot of anesthetic challenges that were new to us because of the rarity of that complication. In addition, it was another situation where the trans-esophageal echocardiography was found very useful and affected the decision making by visualizing the screws inside the aorta. The outcome was successful, and the patient was discharged home safely, hence, we would like to share our experience in managing this difficult case to help others who might find themselves in a similar situation.